Monitoring microalgal growth of Chlorella minutissima with a new all solid‐state contact nitrate selective sensor. (6th March 2022) - Balkanlı, Nihat Erdem; Işıldak, İbrahim; İnan, Benan; Özer, Tuğba; Özçimen, Didem
Abstract: As third generation feedstock, microalgae are microorganisms that can grow only in the optimum conditions. There are parameters including the concentration of macro and microelements in nutrient solution, pH, temperature and light intensity that have significant impact on microalgal growth. In recent years, various sensing devices have been developed for sensitive measurement of these parameters during microalgal growth. In this study, a new potentiometric nitrate selective sensor was developed to indicate the nitrate uptake of microalgae and the effect of nitrate nutrient on microalgal growth, specifically, and this sensor was successfully applied to determine nitrate concentration in medium during microalgal growth. Moreover, the effects of nitrate, carbonate and phosphate concentration in the growth medium on biomass production of Chlorella minutissima were investigated by using Box–Behnken design method, and optimum conditions were determined for the highest biomass production of microalgae. As a result of the experiments, it was seen that the highest C. minutissima production was achieved using the medium consist of 2.63 g/L NaNO3, 0.35 g/L Na2 CO3 and 0.4 g/L KH2 PO4. Statistically, it was observed that there was a proportional relationship between the microalgae production and investigated parameters such as carbon, nitrogen and phosphate amounts of culture mediums. The electrode showed a wide linear range between 1.0 × 10 −1 and 5.0 × 10 −5  M with a detection limit of the 5 × 10 −6  M and the response time was found as 10 s. The results showed that developed nitrate selective sensor could be successfully applied for continuous measurement of nitrate in microalgal productions at reduced cost.